2002
DOI: 10.1097/00005131-200207000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Nonunions Following Intramedullary Nailing of Femoral Shaft Fractures

Abstract: Exchange nailing without extracortical bone grafting seems to be the most effective method to treat a disturbed union of a femoral shaft fracture after intramedullary nailing. Autogenous extracortical bone grafting alone proved to be insufficient. Dynamization predisposed to shortening of the bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(122 citation statements)
references
References 38 publications
3
104
0
6
Order By: Relevance
“…Intramedullary nails in distal shaft or comminuted fractures of the femur are also not canal-filling which reduces stability in bending and rotation. Too much motion in those complex fractures results in unpredictable mechanical strength and some non-union [10]. This small subset of cases may require more stability than that is afforded by interlocking intramedullary nailing [6].…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary nails in distal shaft or comminuted fractures of the femur are also not canal-filling which reduces stability in bending and rotation. Too much motion in those complex fractures results in unpredictable mechanical strength and some non-union [10]. This small subset of cases may require more stability than that is afforded by interlocking intramedullary nailing [6].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to one experiment, the fracture site did not show much resistance to rotational movement within 10-15 degrees when interlocking nails were inserted, suggesting that absolute fixation power at the fracture site by interlocking intramedullary nails was limited. Too much motion in complex fractures resulted in unpredictable mechanical stability and nonunion [12]. This small subset of cases may require more stability than that is afforded by interlocking intramedullary nailing [5].…”
Section: Introductionmentioning
confidence: 99%
“…The retained nail acts as a useful loadsharing device, neutralising shear forces at the fracture site and maintaining alignment of the fracture [12]. Choi et al [2] reported successful bony union with plate augmentation leaving the nail in situ for unstable femoral nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…이에 대한 치료로 역동화, 골이식, 금속정 교체술, 금속판 변환술, 금속판 보강술 등이 사용되 고 있다. 이 중 금속정 교체술은 확공 후 보다 큰 직경의 금속정으로 교체하는 방법으로 현재 가장 널리 시행되고 있으며 4,5,13,20) 이의 초기 결과는 매우 우수한 것으로 알려 져 왔으나, 최근 여러 연구에서 예상했던 것보다 열등한 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 69 73 45 56 43 28 73 71 56 35 37 59 44 41 72 53 37 결과가 보고되었다 11,21) . , 최근 보다 다양하고 복잡한 골절과 접하게 되고 골수 내 금속정의 사용 빈도가 증가하면서 불유합의 빈도가 4.1-12% 까지 보고되고 있다 14,16,18) .…”
Section: 서 론 성인 대퇴골 간부 골절의 치료로 골수 내 금속정 고정술 은 가장 이상적인 치료 방법으로 알려져 있으며unclassified